Comparative evaluation of vegetable matter involved lesions with oral parasitic infections in the oral cavity - Pinheiro, Tiago Novaes; Leite, Milena Gomes Melo; da Silva, Cristiane Cantiga [UNESP]; Alexandre, Cleber Nunes; Cabral, Lioney Nobre; Carvalho, Hannah Marcelle Paulain; de Souza, Daniel Frota; Gonçalves, Jéssica Lourdes de Aguiar; de Souza, Thales Edecherly Nasserala; Melo, Nara Deise de Souza; Cintra, Luciano Tavares Angelo [UNESP]; Kanehira, Beatriz Terumi Barreto; et al. (Wiley, 2022)
The current research aims to perform a comparative evaluation of vegetable matter involved lesions with oral parasitic infections found in oral mucosa, presenting histochemical methods to differentiate their microscopic similarities. Eight cases were selected out of a sample of 1.975 reports from a single Oral and Maxillofacial Pathology Service of the author's institution from 2012 to 2019. Specimens were examined by hematoxylin and eosin staining (HE), periodic acid-Schiff (PAS) staining, Gomori–Grocott staining, Ziehl–Neelsen staining, Giemsa, and mucicarmine staining. Microscopic analysis included fluorescence, polarized light, and confocal microscopy. Microscopically, in HE coloration, hookworm eggs showed as eosinophilic. Inflammatory multinucleated giant cells and lymphocytes, were usually related to the nematode eggs, forming an intense inflammatory infiltrate. Biofluorescent properties of eggs and larvae revealed to be sensitive in the detection of parasitic structures contrasting with the inflamed connective tissue. Vegetable presence was confirmed by polarized light microscopy and it was found to be associated with microbial biofilms. Confocal microscopy has showed to be an excellent method for morphotype differentiation of parasitic eggs. Parasitic infection and vegetable matter displayed similarities in the inflammatory response, but the latter can rot and agglomerate biofilms. The microscopic diagnosis of such infections requires the interpretation of challenging morphological features since the parasites are usually sectioned and mixed with an inflammatory reaction. These histochemical approaches proved to be excellent to distinguish both lesions.
Keywords: ancylostomiasis; denture; hookworm; oral parasite; vegetable matter